Construing EFL Students’ Beliefs on the Inclusion of Inner Circle Cultures in English Language Teaching - M. Faruq Ubaidillah (Lingual, 2019)
This study was an attempt to uncover EFL students’ beliefs of inner circle (IC) cultures in their English language classes. Thirty-four English department students (henceforth, participants) were recruited by means of convenience sampling technique. They were asked to fill out a set of questionnaires and provided reasons of the answers. The results of this study yielded that the participants’ belief systems were seen complex. It is proven from three varied voices of the inner circle inclusion in their English language classes; 65 % of the participants agreed to include inner circle culture, 21 of them refused it, and 15% of them held a neutral belief. Suggestions for future research are offered at the end of this paper.